FLORISTIC COMPOSITION OF THE INTERFACE OF A SEASONAL SEMIDECIDUOUS FOREST WITH A PASTURE - Silva, Marcele Almeida; Rodrigues, Mariane Martins; Righi, Ciro Abbud (REVISTA DE AGRICULTURA, 2018)
In this study, the floristic composition of the interface of the seasonal semideciduous forest inserted in a pasture matrix was evaluated. Three transects of 10 m wide by 50 m long from the edge to the center of the fragment were installed systematically. Few species were responsible for more than half of the individuals, contributing to the low species richness detected. Bauhinia forficata and Urera baccifera have represented almost 40% of the individuals sampled. Besides this, a high density of pioneer species and abundance of few species up to 50 m were verified, confirming that the edge effect extends itself beyond the sampled distance. Future studies must perform samplings in bigger transactions in order to verify the extent of the edge effect on plant community.